Clinical phenotypes and outcomes of heritable and sporadic pulmonary veno-occlusive disease: a population-based study. Issue 2 (February 2017) - Montani, David; Girerd, Barbara; Jaïs, Xavier; Levy, Marilyne; Amar, David; Savale, Laurent; Dorfmüller, Peter; Seferian, Andrei; Lau, Edmund M; Eyries, Mélanie; Le Pavec, Jérôme; Parent, Florence; et al.
Summary: Background: Bi-allelic mutations of the EIF2AK4 gene cause heritable pulmonary veno-occlusive disease and/or pulmonary capillary haemangiomatosis (PVOD/PCH). We aimed to assess the effect of EIF2AK4 mutations on the clinical phenotypes and outcomes of PVOD/PCH. Methods: We did a population-based study using clinical, functional, and haemodynamic data from the registry of the French Pulmonary Hypertension Network. We reviewed the clinical data and outcomes from all patients referred to the French Referral Centre (Pulmonary Department, Hospital Kremlin-Bicêtre, University Paris-Sud) with either confirmed or highly probable PVOD/PCH with DNA available for mutation screening (excluding patients with other risk factors of pulmonary hypertension, such as chronic respiratory diseases). We sequenced the coding sequence and intronic junctions of the EIF2AK4 gene, and compared clinical characteristics and outcomes between EIF2AK4 mutation carriers and non-carriers. Medical therapies approved for pulmonary arterial hypertension (prostacyclin derivatives, endothelin receptor antagonists and phosphodiesterase type-5 inhibitors) were given to patients according to the clinical judgment and discretion of treating physicians. The primary outcome was the event-free survival (death or transplantation). Secondary outcomes included response to therapies for pulmonary arterial hypertension and survival after lung transplantation. A satisfactory clinical response to specific therapy for pulmonary arterial hypertension was defined by achieving New York Heart Association functional class I or II, a 6-min walk distance of more than 440 m, and a cardiac index greater than 2·5 L/min per m 2 at the first reassessment after initiation of specific therapy for pulmonary arterial hypertension. Findings: We obtained data from Jan 1, 2003, to June 1, 2016, and identified 94 patients with sporadic or heritable PVOD/PCH (confirmed or highly probable). 27 (29%) of these patients had bi-allelic EIF2AK4 mutations. PVOD/PCH due to EIF2AK4 mutations occurred from birth to age 50 years, and these patients were younger at presentation than non-carriers (median 26·0 years [range 0–50.3] vs 60·0 years [6·7–81·4] years; p<0·0001). At diagnosis, both mutations carriers and non-carriers had similarly severe precapillary pulmonary hypertension and functional impairment. 22 (81%) of mutations carriers and 63 (94%) of non-carriers received therapy approved for pulmonary arterial hypertension. Drug-induced pulmonary oedema occurred in five (23%) of treated EIF2AK4 mutations carriers and 13 (21%) of treated non-carriers. Follow-up assessment after initiation of treatment showed that only three (4%) patients with PVOD/PCH reached the predefined criteria for satisfactory clinical response. The probabilities of event-free survival (death or transplantation) at 1 and 3 years were 63% and 32% in EIF2AK4 mutations carriers, and 75% and 34% in non-carriers. No significant differences occurred in event-free survival between the 2 groups (p=0·38). Among the 33 patients who had lung transplantation, estimated post-transplantation survival rates at 1, 2, and 5 years were 84%, 81%, and 73%, respectively. Interpretation: Heritable PVOD/PCH due to bi-allelic EIF2AK4 mutations is characterised by a younger age at diagnosis but these patients display similar disease severity compared with mutation non-carriers. Response to therapy approved for pulmonary arterial hypertension in PVOD/PCH is rare. PVOD/PCH is a devastating condition and lung transplantation should be considered for eligible patients. Funding: None.